Legal Protection of the Rights of Trade Secret Information Owners in Employment Agreements That Do Not Include a Trade Information Confidentiality Clause - Sinaga, Sudarman; Purba, Hasim; Siregar, Mahmul; Aprilyana S., Idha (JOM, 2024)
A Trade Secret refers to knowledge or information that is not publicly accessible within the realms of technology and business, which holds economic significance due to its utility in commercial operations, and is carefully safeguarded by its proprietor. Such secrets receive legal protection upon the creation of the information, especially when it begins to influence economic activities. It is common for parties to insert confidentiality clauses into agreements to ensure that sensitive information remains undisclosed. Once included, compliance with the confidentiality terms becomes mandatory for all involved. This study examines the responsibilities of employees, bound by employment contracts, in preserving the confidentiality of trade secrets belonging to their employers. It also explores the legal consequences of employment contracts that omit confidentiality clauses and the overall legal protection afforded to owners of trade secrets under Indonesia's legal framework. The study adopts a normative legal research approach, relying primarily on secondary data sources. Using a descriptive analysis method, data was collected through the examination of documents. The findings reveal that employees are obligated to protect their employer's trade secrets, and the manner in which companies manage their confidential information greatly impacts employees' ability to uphold such secrecy. A key measure in protecting trade secrets is for employers to establish provisions in employment contracts with their staff. Without confidentiality clauses, the risk of sensitive information being leaked or misused by the recipient is significantly heightened.